Influence of Government Accounting Standards, Systems Internal Control, Regulatory Compliance Legislation on Quality Financial Statements - Yasis, Ulin (International Journal of Science and Society, 2024)
This research aims to examine the impact of variables such as government accounting standards, internal control systems, and statutory laws on the quality of financial reporting. This study employs a quantitative methodology grounded in a positivist perspective. This research is explanatory in nature and employs a purposive sample strategy, which involves selecting participants based on specific criteria or factors. Based on the findings of hypothesis testing, it can be inferred that the variables related to the implementation of SAP, SPI, and compliance with statutory regulations have a substantial impact on the quality of financial reports, both collectively and individually.